The increasing chronicity of HIV in sub-Saharan Africa: Re-thinking "HIV as a long-wave event" in the era of widespread access to ART - Whiteside Alan; Hanass-Hancock Jill; Nixon Stephanie A; Barnett Tony (BMC, 2011)
Abstract HIV was first described as a "long-wave event" in 1990, well before the advent of antiretroviral therapy (ART). The pandemic was then seen as involving three curves: an HIV curve, an AIDS curve and a curve representing societal impact. Since the mid-2000's, free public delivery of life-saving ART has begun shifting HIV from a terminal disease to a chronic illness for those who can access and tolerate the medications. This increasing chronicity prompts revisiting HIV as a long-wave event. First, with widespread availability of ART, the HIV curve will be higher and last longer. Moreover, if patterns in sub-Saharan Africa mirror experiences in the North, people on ART will live far longer lives but with new experiences of disability. Disability, broadly defined, can result from HIV, its related conditions, and from side effects of medications. Individual experiences of disability will vary. At a population level, however, we anticipate that experiences of disability will become a common part of living with HIV and, furthermore, may be understood as a variation of the second curve. In the original conceptualization, the second curve represented the transition to AIDS; in the era of treatment, we can expect a transition from HIV infection to HIV-related disability for people on ART. Many such individuals may eventually develop AIDS as well, but after a potentially long life that includes fluctuating episodes of illness, wellness and disability. This shift toward chronicity has implications for health and social service delivery, and requires a parallel shift in thinking regarding HIV-related disability. A model providing guidance on such a broader understanding of disability is the World Health Organization's International Classification of Functioning, Disability and Health (ICF). In contrast to a biomedical approach concerned primarily with diagnoses, the ICF includes attention to the impact of these diagnoses on people's lives and livelihoods. The ICF also focuses on personal and environmental contextual factors. Locating disability as a new form of the second curve in the long-wave event calls attention to the new spectrum of needs that will face many people living with HIV in the years and decades ahead.